Beckman pH Control ends "red water days" in Macon - Beckman Instruments, Inc. (1950)
This advertisement describes a use case for Beckman pH meters in which Macon Water Works used the instruments to control the acidity of the water and inhibit corrosion of pipes. Arnold Beckman invented his first pH meter in 1934 at the request of a chemist from the California citrus industry, who needed an accurate way to measure the acidity of his product. The resulting instrument kicked off rapid development not only of Beckman Instruments, Inc. but also of the electronic scientific instrument industry.
Keywords: Hydrogen-ion concentration--Measurement--Instruments; Scientific apparatus and instruments; Georgia--Macon; Corrosion and anti-corrosives; Beckman Instruments, Inc.; Water quality; Water quality management; Water